Clark Freeport Casino-Hotel Complex - Seco, Renz Jerome D.; Silvestre, Jose Danilo A. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
The Clark Freeport Casino-Hotel Complex is a study which primarily aims to come up with an efficient redefinition of an entertainment, gaming and accommodations facility which caters to the needs of its users through an environment that would stimulate an excitement and relaxation. The study examined different aspects of the entertainment and gaming tourism industry of the Philippines and all other factors relating to its economic growth and development, its contribution to the country's economy and its impact in a community. Despite the negative impact of the gambling in a community it is undeniable that the entertainment and gaming tourism industry is really a major factor for a countries economic growth and development, its existence in a community greatly affect not only the national level but it affects greatly the locals of the community. Based on research and analysis, it is very possible that the Philippines will be one of the prime casino destinations in Asia. Specifically, the Clark Freeport Zone as the chosen site for the study is likely to be the next entertainment and gaming hub in the Philippines. Its location, being geographically accessible in almost all parts of the Philippines and the world due to its proximity to an international gateway and via the national highways of the Luzon (NLEX and SCTEx) is just a factor for the success of such establishments in the region. The study concludes that aesthetics is also a major factor in the success of a casino-hotel establishment. Fake as it may seem, but this artificial beauty is one of the key players in the creation of a cultural identity and trademark for these is what retains in the minds of the guests that visited the place, especially in the case of a casino-hotel complex.
Includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Clark Freeport Casino-Hotel Complex (Clark).; Casinos -- Clark Freeport Zone